STATIN SAFETY REVISITED DATA - O. M. Drapkina (Столичная издательская компания, 2015)
Questions of statins use in liver diseases are discussed. Data from clinical studies on statins safety in cardiac patients with liver diseases are presented. Features of statins use in nonalcoholic fatty liver disease, viral hepatitis C are considered separately.